Effect of preparation conditions on the electro-optical performance and the polymer morphology of polymer-dispersed liquid crystals with polyhedral oligomeric silsesquioxane (POSS) microstructure. Issue 1 (13th April 2022) - Yu, Ping; Zhao, Yuzhen; He, Zemin; Zhang, Huimin; Zhao, Yang; Zhang, Yongming; Guo, Zhun; Ma, Cheng; Gao, Jianjing; Zhang, Haiquan
Abstract: In this work, the effects of the preparation conditions on the electro-optical performance and the polymer morphology of the polymer dispersed liquid crystal (PDLC) samples in which the polymer matrix contained polyhedral oligomeric silsesquioxane (POSS) microstructure were studied. The results confirmed the dramatic improvement effect of POSS microstructure for the electro-optical properties of PDLC. Moreover, the electro-optical performance and the polymer morphology of the PDLC samples with POSS microstructure can be regulated successfully by the preparation conditions, such as UV light intensity and polymerization temperatures. This work can provide a way for regulating methods for PDLC films.